2018
DOI: 10.32800/abc.2018.41.0389
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II DRB variability in wild black howler monkeys (Alouatta pigra), an endangered New World primate

Abstract: MHC class II DRB variability in wild black howler monkey (Alouatta pigra), an endangered New World primate. The genes of the major histocompatibility complex (MHC) are the most important genetic component of the immune system in vertebrates. Their variability is known to influence a species' ability to recognize and respond to pathogens. Here, we present the first data of the MHC class II DRB exon 2 for the endangered black howler monkey (Alouatta pigra), one of the most northerly distributed platyrrhines. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…This result is consistent with the non-aggressive and promiscuous behaviour of muriquis and with a scramble rather than contest model of male reproductive competition [79]. Indeed, in contrast to chimpanzees, where alpha males sire a smaller share of infants as the number of male competitors increases [29,32], we found the opposite pattern in muriquis, with reproductive skew slightly higher for the cohort with more potential male competitors (31 versus 27). Instead, patterns of female mate choice and the social influence of adult males' mothers seem to have a bigger impact on the variation we observe in muriquis, with matriarchs and their adult sons possibly collaborating to mutually increase each other's fitness [24].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result is consistent with the non-aggressive and promiscuous behaviour of muriquis and with a scramble rather than contest model of male reproductive competition [79]. Indeed, in contrast to chimpanzees, where alpha males sire a smaller share of infants as the number of male competitors increases [29,32], we found the opposite pattern in muriquis, with reproductive skew slightly higher for the cohort with more potential male competitors (31 versus 27). Instead, patterns of female mate choice and the social influence of adult males' mothers seem to have a bigger impact on the variation we observe in muriquis, with matriarchs and their adult sons possibly collaborating to mutually increase each other's fitness [24].…”
Section: Discussionsupporting
confidence: 87%
“…We focused on the DRB1 gene, and particularly on exon 2, which contributes to coding the structure of the extracellular antigen-binding region. This gene is exceptionally polymorphic and is the most commonly screened locus in studies of MHC variation in nonhuman primates [30][31][32][33][34][35]. MHC allele calling was performed using the AmpliSAS pipeline [36].…”
Section: Methods (A) Sampling and Laboratory Proceduresmentioning
confidence: 99%
“…Since then, research on the MHC of non-human primate (NHP) species has intensified, and most often concerns species that are models for human biology and disease. In addition, there has also been a steady growth in the MHC content-derived diverse NHP species that are studied for conservation biology purposes (Cao et al 2015;de Groot et al 2017a, b;Hans et al 2017;Maibach et al 2017;Wroblewski et al 2017;Arguello-Sanchez et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While few studies have thoroughly examined wild populations of platyrrhines to shed light on MHC-related questions, the limited studies suggest a diverse and variable system. To date, studies of Class II MHC in wild populations of platyrrhines have revealed some diversity in the DP and DQ genes, and extensive variation in DR genes (Aotidae [ 5 , 20 23 ]; Alouatta pigra [ 24 ]).…”
Section: Introductionmentioning
confidence: 99%